The need analysis for developing peer mentors as peer counseling program among Gen Z - Pandang, Abdullah; Rivai, Mantasiah; Umar, Nur Fadhilah; Arifyadi, Azzam (International Journal of Research in Counseling and Education, 2022)
This study aims to describe a picture of the perception of positive communication from Gen Z and lecturers, as well as to describe a picture of program needs, potentials in developing peer mentor programs. The type of research is descriptive quantitative and research data is collected using research instruments intended for lecturers and students in measuring the needs of peer mentor programs, this instrument uses a modified Likert scale model. The sampling technique used is simple random sampling with a total sample of 1050 students and 121 lecturers consisting of 3 provinces in South Sulawesi, West Sulawesi, and Central Sulawesi. Then analyzed using descriptive analysis techniques using the JASP application which describes items in 5 categories, namely very low, low, medium, high, and very high. From the data analysis carried out, the results obtained are: 1) Generation Z's perception of communication patterns is in the very high category and classified as polite, 2) Lecturers' perceptions tend to view generation Z's communication patterns as lacking in terms of 3 aspects, namely understanding of politeness in communicating, behavior polite in communication and awareness of the importance of polite behavior, 3) Development of peer mentor models as an effort to develop positive communication and polite behavior in the language of generation z is included in the very high category.